2020
DOI: 10.1111/pbi.13429
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated knockout and overexpression studies reveal a role of maize phytochrome C in regulating flowering time and plant height

Abstract: Maize is a major staple crop widely used for food, feedstocks and industrial products. Shadeavoidance syndrome (SAS), which is triggered when plants sense competition of light from neighbouring vegetation, is detrimental for maize yield production under high-density planting conditions. Previous studies have shown that the red and far-red photoreceptor phytochromes are responsible for perceiving the shading signals and triggering SAS in Arabidopsis; however, their roles in maize are less clear. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 59 publications
(105 reference statements)
0
37
0
Order By: Relevance
“…Moreover, it was shown that GmCRY1s play important roles in mediating LBL-induced SAS through modulating GA metabolism (Lyu et al 2020). Other studies in maize reported that the Zmphyb1 Zmphyb2 double mutant displays constitutive shade avoidance responses, while Zmphyc1 Zmphyc2 double mutant shows moderately early flowering under long-day conditions (Kebrom et al 2006;Li et al 2020;Sheehan et al 2007). Furthermore, expression of these two hyperactive mutant forms of ZmPHYB1 or overexpression of ZmPHYCs effectively reduces the plant height and ear height of mature maize plants in field conditions (Li et al 2020;Zhao et al 2020).…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Moreover, it was shown that GmCRY1s play important roles in mediating LBL-induced SAS through modulating GA metabolism (Lyu et al 2020). Other studies in maize reported that the Zmphyb1 Zmphyb2 double mutant displays constitutive shade avoidance responses, while Zmphyc1 Zmphyc2 double mutant shows moderately early flowering under long-day conditions (Kebrom et al 2006;Li et al 2020;Sheehan et al 2007). Furthermore, expression of these two hyperactive mutant forms of ZmPHYB1 or overexpression of ZmPHYCs effectively reduces the plant height and ear height of mature maize plants in field conditions (Li et al 2020;Zhao et al 2020).…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Tissue culture has been widely used to advance plant research by transgenesis and gene‐editing technologies (Azeez and Busov, 2021 ; Li et al ., 2020 ; Liu et al ., 2019 ). Although successful regeneration of transformed seedlings has been reported in some species, it is still the bottleneck for the C .…”
Section: Discussionmentioning
confidence: 99%
“…In rice, it plays an important role in FR-mediated repression of flowering under long-day conditions [ 60 ]. In maize, it has been reported to regulate early flowering and plant height [ 61 ]. Thus, phytochrome C could be a plausible candidate gene for the control of stem elongation and flowering.…”
Section: Discussionmentioning
confidence: 99%